An exploration of South African supervisors’ experiences of working with diversity in psychotherapy supervision with trainee psychologists - Mendu, Elvis (My University, 2022)
This study aimed to explore psychotherapy supervisors’ lived experiences of working with racial and cultural diversity within the supervision relationship with trainee psychologists. Specifically, how psychotherapy supervisors think about helping trainees to work with racial and cultural diversity in psychotherapy, as well as how they work with racial and cultural diversity within the supervision relationship itself. Using a qualitative research approach located within an exploratory research design, nine face-to-face interviews were conducted. The interviews were transcribed and analyzed using Braun and Clarke's (2006) thematic analysis. Four dominant themes were identified: a safe space to struggle and think together, thinking about blind spots and personal biases, racial and cultural dynamics as unavoidable, and the experience of being interviewed. The findings of this study correspond to the existing literature on multicultural supervision; however, this study differs in that it problematized the usual power dynamics between a supervisor and trainee, through the positionality of the researcher. Future studies could focus on diversity more broadly, as well as other aspects of diversity such as class, gender, sexual orientation, or religious affiliation. Additionally, it is recommended that future studies include a more heterogeneous sample that may comprise both males and females, all racial categories, and participants from different geographical locations.
A research report submitted in partial fulfilment of the requirements for the degree of MA (Clinical Psychology) in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2022